AJET and the shifting dynamics of educational technology publishing in 2024 - Corrin, Linda; Han, Feifei; Deneen, Chris; Huijser, Henk (Australasian Journal of Educational Technology, 2024)
In this end of year reflection on AJET in 2024, the editorial team consider the achievements of the journal and the changing academic publishing environment in which it operates. We profile two publications that the AJET Lead Editors contributed to this year that address the shifting dynamics of educational technology publishing and what these mean for AJET. These include issues such as the increasing number of journals in the field, the costs associated with academic publishing, engagement in the peer review process, the emergence of generative artificial intelligence, and the ethics and integrity of educational technology research and publication. This is followed by an exploration of the journal’s bibliometrics for 2024. We end with a look at the future directions for AJET as we move into our 40th year of publication.